P3 Towards advanced manufacturing for personalised vascular grafts. (5th April 2020) - Asciak, L; Dow, J; Brodie, R; Maclean, C; Shu, W; McCormick, C
Abstract : Arterial replacement using synthetic grafts is currently the standard of care for patients with arterial aneurysm and/or dissection. These disease states can result in death due to arterial rupture if left untreated. However, the treatment itself, using knitted or woven polyester grafts, can lead to longer term health problems for the patient, including: high blood pressure and heart strain due to the mismatch in compliance between the synthetic graft and the native vessel; problems related to poor bio-integration of the graft prosthesis, including chronic infection; and restricted blood supply to organs due to mismatched geometry of the synthetic graft. The use of synthetic grafts for revascularisation of smaller diameter arteries is limited by very low patency rates, meaning that revascularisation of the coronary circulation still requires the use of autologous grafts. Alternative vascular graft technologies are therefore required. In this study, we have evaluated the potential of alginate as a novel graft material and characterised a rapid manufacturing method for the production of multi-layered synthetic vessels. Alginate hydrogel formation can be easily achieved in the presence of divalent cations, such as calcium or barium, in a process known as ionic crosslinking. To assess the effect of this crosslinking method on the mechanical properties of the gel and whether the chosen material mimics the biomechanical properties of native vessels, alginate gels (4, 5% (w/v)) in disc form using calcium and barium cross-linkers at different concentrations (0.1, 0.2, 0.3M) were mechanically characterised via compression testing. Results showed that ionically crosslinked alginate exhibits a viscoelastic behaviour similar to soft tissue, rendering it a potentially suitable material candidate for blood vessel substitution. A dip-coating method involving the immersion of a stainless-steel mandrel (4 mm diameter) within alginate and cross-linker solutions, yielded multi-layer tubular structures. The resultant tubular vessel constructs were found to be stable within phosphate buffered saline (0.01M, 37 °C) over a period of two weeks. The formulations used in this study are compatible with vascular cells and future work will therefore focus on the development of cell-laden constructs, with the use of 3D printing explored as a means of better matching the vessels produced to the patient's anatomy. It is envisaged that this novel approach, will help accelerate progress towards the development of personalised vascular grafts with optimised biological and mechanical properties, thereby providing improved outcomes for patients. The authors acknowledge the funding support from Terumo Aortic, SRPe NMIS-IDP (L. Asciak) and EPSRC (J. Dow, Grant No.: EP/L015595/1).